International trade, economic crisis and the sustainable development goals - Chatterjee, Tonmoy (Emerald Publishing Limited, 2024)
In an ever-shrinking world, the intricate web of international trade has bound nations together in unprecedented ways. The flow of goods, services and ideas across borders is a testament to human ingenuity and cooperation. Yet, the ripples of economic crises, whether spurred by financial meltdowns or unforeseen sociopolitical turmoil, remind us of the fragility that underlies our global economic system. As the deadline for the United Nations' 2030 Sustainable Development Goals (SDGs) looms before us, International Trade, Economic Crisis and the Sustainable Development Goals delves into the nuances of international trade dynamics, the causes and consequences of economic crises and the alignment of these forces with the SDGs. Together, chapters seek to answer pressing questions: How can international trade be harnessed to foster sustainable development? What strategies can nations employ to weather economic storms while staying true to the SDGs? How do we reconcile the pursuit of economic growth with environmental and social responsibility? Proposing international trade as a path for achieving the SDGs, this curated collection envisions a more equitable and sustainable world, one where the benefits of international trade are fairly distributed, where economic crises are met with resilience and innovation and where the SDGs are not just aspirations but lived realities.
Keywords: Sustainable development.; International trade.; Sustainable development reporting.; Business & Economics -- Development -- Sustainable Development.; International trade and commerce.; Development economics and emerging economies.; Sustainability.; elektronické knihy; electronic books